Study the Toxic Effect of N-nitroso dimethylamine on Testes and Kidney: Oxidative Stress Damage through Histopathological Analysis - Abbas A. Khudhair; Bushra I. Al-Kaisie (International Journal of Medical Toxicology and Legal Medicine, 2024)
Because the lack of sufficient studies about the effect of NDMA on kidney and testes tissues in addition to the focusing on liver toxicity research, thus this study is performed to evaluate such damage. Forty-five male rats were used in the study as follow; GI: control group, GII: treated with (3mg/kg NDMA) and GIII: treated with (1.5 mg/kg NDMA) intra-peritonially 3 times a week for 3 months. After completion of the study periods, blood sample were collected for biochemical analysis, tissue sample (kidney and testes) also taken for histopathological study. Result reveals a significant (P<0.05) increase in serum level of MDA and BUN in groups treated with NDMA in comparison to control. However, there is a significant (P<0.05) decrease in serum CAT and GSH in NDMA treated groups when compared to control. Histopathological study of kidney show area of atrophy of glomeruli, vacuolation and tubular epithelial degeneration and necrosis. On the other hands, testes presented with distortion of seminiferous tubules, vacuolation and necrosis of germinal layers along with suppression of spermatogenesis and absence of sperm in NDMA when compared to control groups. In conclusion, NDMA produce oxidative stress; which adversely affect both renal and testicular tissue along with their architecture distortion and impaired function.